Global challenge and spiritual security (Journal of Philosophy Culture and Political Science, 2015)
The work demonstrates the analysis of problems globalization . In the age of globalization, inter cultural dialogue and tolerance thinking are critically important for the development of a civilization and culture in the world. Religious leaders have a great resolve to formation human security of global world. The author tries to show how the process of formation the modern Islamic societies and problem of religion identity.At the end author gives suppositions on actual questions on the world religious tendencies.
Keywords: Global world; dialogue; tolerance; stability; extremism; terrorizm; society; the state; politics; identity; Islam religion.